2001
DOI: 10.1182/blood.v98.4.913
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways activated by daunorubicin

Abstract: The anthracycline daunorubicin is widely used in the treatment of acute nonlymphocytic leukemia. The drug has, of course, been the object of intense basic research, as well as preclinical and clinical study. As reviewed in this article, evidence stemming from this research clearly demonstrates that cell response to daunorubicin is highly regulated by multiple signaling events, including a sphingomyelinase-initiated sphingomyelin-ceramide pathway, mitogen-activated kinase and stress-activated protein/c-Jun Nter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 168 publications
(135 reference statements)
6
118
0
Order By: Relevance
“…However, because we found that suppression of polo-like kinase 1 by small-interfering RNA did not affect anthracycline-induced PinX1 downregulation (data not shown), we exclude that anthracycline stimulates PinX1 degradation through the reported polo-like kinase 1 pathway. It was reported that anthracyclines can activate some kinds of protein kinases, which may phosphorylate different proteins and resulting in their degradation (Laurent and Jaffrezou, 2001;Small et al, 2003). As PinX1 contains many potential phosphorylation sites, we speculate that the degradation of PinX1 stimulated by anthracyclines might be through kinase pathways other than the polo-like kinase 1 pathway.…”
Section: Discussionmentioning
confidence: 85%
“…However, because we found that suppression of polo-like kinase 1 by small-interfering RNA did not affect anthracycline-induced PinX1 downregulation (data not shown), we exclude that anthracycline stimulates PinX1 degradation through the reported polo-like kinase 1 pathway. It was reported that anthracyclines can activate some kinds of protein kinases, which may phosphorylate different proteins and resulting in their degradation (Laurent and Jaffrezou, 2001;Small et al, 2003). As PinX1 contains many potential phosphorylation sites, we speculate that the degradation of PinX1 stimulated by anthracyclines might be through kinase pathways other than the polo-like kinase 1 pathway.…”
Section: Discussionmentioning
confidence: 85%
“…The mitochondrial pathway to cell death plays an essential role in apoptosis induced by cytotoxic agents, including the podophyllotoxin derivative etoposide (Schmitt et al, 1999), the anthracyclins such as daunorubicin (Laurent and Jaffrezou, 2001) and the nucleotide analog cytarabin (Hiddemann, 1991), three cytotoxic drugs commonly used for treating AMLs. This pathway leads to cytochrome c-and Apaf-1-mediated activation of caspase-9, a first step in a proteolytic cascade that involves effector caspase-3, -6 and -7 (Dubrez et al, 1996;Slee et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…100 Malignant cells exhibiting constitutive NF-kB activation are relatively resistant to chemo-or radiotherapy, and NF-kB inhibitors increase their sensitivity to such anticancer treatments, 3,101 presumably by downmodulating antiapoptotic NF-kB target genes such as c-IAPs, c-FLIP, Bcl-2, and Bcl-X L . 5 In B-precursor acute lymphoblastic leukemia (ALL), the most common pediatric malignancy, NF-kB is activated by treatment with anthracyclines, known to favor the nuclear translocation of NF-kB subunits, 102 or by irradiation. 103 Pharmacologic inhibition of NF-kB restored or enhanced apoptosis in doxorubicin-treated primary ALL cells.…”
Section: Therapeutic Strategies Targeting Nf-jbmentioning
confidence: 99%